ANALISIS TINGKAT EFISIENSI BELANJA LANGSUNG PADA SEKRETARIAT DAERAH KOTA TOMOHON - Gerung, Ireyne R.; Kalangi, Lintje; Pusung, Rudy J. (Universitas Sam Ratulangi, 2020)
Budget is important to help all activities carried out in the company or agency. The purpose of this study is to know the level of direct spending management efficiency. The method of this study is a qualitative with descriptive method. The results show that the efficiency levels are excellent. The level of efficiency in the year 2016 with a efficiency rate of 65.04%, year 2017 with a efficiency rate of 65.14% and year 2018 with a efficiency rate of 67.31%. On year of 2016 to 2018 as overall its efficiency level is in efficient category which means there is a good managing for existing budgets with minimum budget usage for maximum results.